Intimni mediji in generacijska struktura občutenja - Luthar, Breda (Družboslovne razprave, 2018)
The article argues for audience studies that draw on the analysis of artefactual, spatial, temporal and sensorial aspects of media consumption and build on so-called medium theory and the theory of practice in sociology. In part two of the article, we interpret the results of a qualitative empirical study regarding the daily use of media technology among young people aged 19-29 years. The study finds that the circumstances in which digital media have colonised all spheres of public life and in which online social life has become completely naturalised have led to constant online connectivity as well as highly fragmented and dispersed communication practices of users as they move among different media. The analysis of media consumption diaries points to radical mediatisation, which is playing an important role in the changing generational structure of feeling.
Keywords: digitalni mediji; mladi; občinstvo; občutenje; Slovenija; sociologija vsakdanjega življenja; tehnologija